Carveol, a natural monoterpene from essential oils prevents neuronal impairments associated with murine Parkinson's disease model in rats - Ola A. Habotta; Lashin Saad Ali; Rami B. Kassab; Qinghua Zhang; Maoyong Zheng; Barakat M. Alrashdi; Jehad Zuhair Tayyeb; Motasim Jawi; Mohamed A. Elhefny; Hassan Al Sberi; Dina Abd-Eldaim; Omer Abdelbagi; et al. (Journal of Agriculture and Food Research, 2025)
Carveol (CR), a natural monocyclic monoterpenoid alcohol with various biological activities. In this investigation, we aimed to scrutinize the neuromodulatory and neuroprotective impact of CR on neuronal damage associated with rotenone (Rt)-mediated-Parkinson's disease (PD) murine model. Rats were placed into six groups: control, PD model [received Rt (2 mg/kg)], CR (20 mg/kg), Rt + CR1 (10 mg/kg), Rt + CR2 (20 mg/kg), and Rt + sinemet treatment (12 mg/kg). CR administration improved the motor function and modulated the disrupted neurotransmitters system, as demonstrated by the enhancement of dopamine, serotonin, gamma-aminobutyric acid, and acetylcholinesterase activity. The neuromodulatory efficiency of CR was extended to increase brain-derived neurotrophic factor and tyrosine hydroxylase activity, while inhibited the accumulation of α-synuclein in the striatum. Notably, CR administration upregulated the nuclear factor erythroid 2–related factor 2/heme oxygenase 1 antioxidant signaling, boosted glutathione, catalase, glutathione peroxidase, superoxide dismutase activities, while decreased malondialdehyde and nitric oxide in the striatum. Interestingly, CR exhibited persuasive anti-inflammatory activities by inhibiting receptor for advanced glycation endproducts/nuclear factor kappa-B signaling and astrocytes activation, as demonstrated by declined glial fibrillary acidic protein expression, tumor necrosis factor-alpha, interleukin-1 beta, and interleukin-6 levels. Furthermore, CR treatment attenuated neuronal loss by regulating B-cell lymphoma 2 protein/caspase-3 apoptotic signaling. Histopathological examination of striatum and substantia nigra validated the abovementioned results. Collectively, CR treatment revealed multi-target therapeutic agent for PD through the modulation of neuroinflammation, oxidative damage, neurotransmission, and cell survival signaling.